2017
DOI: 10.1177/1071100717745502
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Particulated Juvenile Cartilage Allograft Transplantation for Osteochondral Lesions of the Talus

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…There were 8 studies identified with a total of 171 patients. 3,4,9,12,23,24,51,55 An overview of the study characteristics, patient characteristics, and outcomes within this group is shown in Table 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 8 studies identified with a total of 171 patients. 3,4,9,12,23,24,51,55 An overview of the study characteristics, patient characteristics, and outcomes within this group is shown in Table 8.…”
Section: Resultsmentioning
confidence: 99%
“… a N/A, not available; RTS, return to sports. b References 3, 4, 9, 12, 23, 24, 51, 55. c Range of means of original data.…”
Section: Resultsmentioning
confidence: 99%
“…Coetzee et al 44 found that the clinical improvements diminished when treating defects larger than 150 mm 2 . Dekker et al 47 found that 6 of 15 patients (40%) were clinical failures. The authors concluded that defects larger than 125 mm 2 were prone to failure.…”
Section: Discussionmentioning
confidence: 99%
“…After 25 months, the authors found a significantly higher AOFAS (American Orthopaedic Foot & Ankle Society) score for the PJAC group (97.02) compared with the bone marrow concentrate group (71.33). 46 In 2018, Dekker et al 47 followed 15 patients for 34 months. There was a 40% failure rate, and the predictors of poor outcome were found to be male gender and lesion size greater than 125 mm 2 .…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation